Impaired Chaperone Activity of Human Heat Shock Protein Hsp27 Site‐Specifically Modified with Argpyrimidine. Issue 38 (21st July 2016) - Matveenko, Maria; Cichero, Elena; Fossa, Paola; Becker, Christian F. W.
Abstract: Non‐enzymatic posttranslational modifications (nPTMs) affect at least ∼30 % of human proteins, but our understanding of their impact on protein structure and function is limited. Studies of nPTMs are difficult because many modifications are not included in common chemical libraries or protein expression systems and should be introduced site‐specifically. Herein, we probed the effect of the nPTM argpyrimidine on the structure and function of human protein Hsp27, which acquires argpyrimidine at residue 188 in vivo. We developed a synthetic approach to an argpyrimidine building block, which we then incorporated at position 188 of Hsp27 through protein semisynthesis. This modification did not affect the protein secondary structure, but perturbed the oligomeric assembly and impaired chaperone activity. Our work demonstrates that protein function can be altered by a single nPTM and opens up a new area of investigation only accessible by methods that allow site‐selective protein modification. Abstract : Underinvestigated protein modifications : The non‐enzymatic posttranslational modification (nPTM) argpyrimidine (Apy) was incorporated into Hsp27 through protein semisynthesis, and the impact was investigated at the molecular level. Apy was found to reduce Hsp27 chaperone activity and oligomerization, without affecting folding. This suggests that nPTMs are able to alter protein function.